A Natural History of Time. - Richet, Pascal (University of Chicago Press, 2009)
The quest to pinpoint the age of the Earth is nearly as old as humanity itself. For most of history, people trusted mythology or religion to provide the answer, even though nature abounds with clues to the past of the Earth and the stars. In A Natural History of Time, geophysicist Pascal Richet tells the fascinating story of how scientists and philosophers examined those clues and from them built a chronological scale that has made it possible to reconstruct the history of nature itself. Richet begins his story with mythological traditions, which were heavily influenced by the seasons and almos.